Job Satisfaction among Special Education Teachers Working at Special Education Institutes, Punjab (Pakistan) - Aftab, Muhammad Javed; Rashid, Nadia; Salman, Eman (Annals of Human and Social Sciences, 2023)
This study aims to investigate the level of job satisfaction among special education teachers working at special education institutes in Punjab. Highlighting key factors influencing their satisfaction levels. Special education teachers play a crucial role in the education system, yet their job satisfaction remains underexplored. A quantitative approach was employed, utilizing self made questionnaire of job satisfaction consisted 35 questions which were covering following factors; Working environment, Professional development, Facilities and resources, Implementation of policies, Income, Joy, and Student teacher ratio. Results indicate that senior teachers were more satisfied then junior teachers. Not significant differences were found in job satisfaction level on the basis of gender. Significant group variations were noted on the basis of experience and income. These findings underscore the importance of addressing various facets of job satisfaction. Inform policy interventions aimed at enhancing job satisfaction and ultimately improving the quality of education provided to special students.